Effects of autoregulatory progressive resistance exercise periodization versus linear periodization on muscular strength and anaerobic power in collegiate wrestlers - Weber, Chris J. (University of Wisconsin--Whitewater, 2015)
The main purpose of this study was to observe the effects of the autoregulatory progressive resistance exercise (APRE) protocol versus linear periodization (LP) on anaerobic and strength performances in collegiate wrestlers. Subjects were randomly assigned to APRE periodization or traditional LP during eight weeks of post-season training from approximately mid-March through mid-May 2015. Subjects participated in two exercise trials to measure muscular strength and anaerobic power, with one exercise trial at the beginning of the eight-week post-season training program and one exercise trial at the end of the eight-week post-season training programs. Both the APRE and LP groups improved their peak and average power from pre-test to post-test in both the upper body and lower body Wingate tests. However, there were no significant differences in lower body peak power p=0.3954), lower body average power (p=0.1181), upper body peak power (p=0.3046), or upper body average power (p=0.9426). When comparing the two groups in the one repetition maximum for the squat, there was no statistical significance (p=0.3061), even though the APRE group increased by 11.42% and LP by 8.03%. In the one repetition maximum for the bench press there was a statistical significance (p=0.0179) with the APRE group increasing strength performance by 11.76% compared to LP group which increased strength performance by only 6.3%. While both APRE and LP increased anaerobic power performances, it seems that the APRE protocol was more efficient at increasing muscular strength along with anaerobic power increases.
This file was last viewed in Microsoft Edge.
Keywords: Periodization training; Wrestling--Training; Exercise; Muscle strength